Analisis Serbuk Silika Amorf (SiO2) Berbahan Dasar Pasir - Stevi Silahooy (Science Map Journal, 2020)
The aim of the research was to synthesize amorphous silica powder (SiO2) made from sand obtained from the Bancar-Tuban area using the hydrothermal-coprecipitation method using 7M NaOH as solvent. The samples obtained were characterized using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Scanning Electron Microscopy (SEM). The characterization results show that there has been an increase in the percentage of weight (wt%) Si from 71.5% to 92.20%. The structure of the silica formed is a with non-uniform particle size with an average size exceeding â‰¥110.09 nm. The results of observations using SEM instruments that were carried out using various variations showed that the SiO2 particle size was not uniform, where the SiO2 powder tended to agglomerate